2020
DOI: 10.31234/osf.io/bhnam
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Media use, attention, mental health and academic performance among 8 to 12 year old children

Abstract: The rise in digital media consumption, especially among children, raises the societal question of its impact on cognition, mental health and academic achievement. Here, we review the impact of three different ways of measuring technology use—total hours of media consumed, hours of video game play and number of media used concurrently—in a study surveying 156 eight-to-twelve year-old children. At stake is the question of whether different technology uses may have different effects, which could explain some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…This reduction of a direct, embodied connection to the physical world raises essential educational questions regarding deficits within the entire spectrum of the human senses in children and young people who are in their most critical stages of physiological/neurological development. The negative effects have been discussed in a wide range of pedagogical, psychological and neurological studies (see Turkle, 2011;Hübner, 2017Hübner, , 2019Koch et al, 2017;Twenge, 2017;Weinzirl et al, 2017;Centers for Disease Control and Prevention (CDC), 2018;Rittelmeyer, 2018;Lutzker, 2020a,b;Cardoso-Leite et al, 2021;Rideout et al, 2022).…”
Section: The Role Of the Senses In Education And Teacher Educationmentioning
confidence: 99%
“…This reduction of a direct, embodied connection to the physical world raises essential educational questions regarding deficits within the entire spectrum of the human senses in children and young people who are in their most critical stages of physiological/neurological development. The negative effects have been discussed in a wide range of pedagogical, psychological and neurological studies (see Turkle, 2011;Hübner, 2017Hübner, , 2019Koch et al, 2017;Twenge, 2017;Weinzirl et al, 2017;Centers for Disease Control and Prevention (CDC), 2018;Rittelmeyer, 2018;Lutzker, 2020a,b;Cardoso-Leite et al, 2021;Rideout et al, 2022).…”
Section: The Role Of the Senses In Education And Teacher Educationmentioning
confidence: 99%
“…Although this topic is of particular interest, we are not aware of any other significant studies on the subject. The majority of studies focus on the relationship between technology use and academic performance which has been the subject of extensive controversial research in recent years considering the reported negative, positive, and null associations (Adelantado-Renau et al, 2019;Mundy et al, 2020;Cardoso-Leite et al, 2021;Morgan et al, 2021;Sampasa-Kanyinga et al, 2022;Tafesse, 2022).…”
Section: Use Of Technologies For Recreational Purposes and Scholastic...mentioning
confidence: 99%
“…Compared with the general VDT operation light environment, the more complex and changeable light environment of the VDT workspace may have multiple compound effects on the work efficiency and physical and mental health of operators (Ranasinghe et al, 2016). However, previous studies on the characteristics of "learning" in video game training mainly focused on the game type (Bediou et al, 2018), training time , and the age of the player (Cardoso-Leite et al, 2021), etc. Although many effects of video game training have been confirmed, there are few studies on whether the game environment, that is, the light environment of the e-sports VDT operation space, affects the "learning to learn" effect of video game training.…”
Section: Introductionmentioning
confidence: 99%